Monetary reference points of managers: An empirical investigation of status quo preferences and social comparisons - Christian Grund; Johannes Martin (Institute for the Study of Labor (IZA), 2012)
We assemble two reference point based concepts of utility in our empirical study: the own previous status quo and social comparisons. We explore the relative relevance of these concepts for total compensation as well as for different parts of the compensation package of managers. Making use of a unique panel data set of managers of the German chemical sector, we find that social comparisons of compensation indeed affect reported job satisfaction. Managers compare their total compensation (and fixed salary) with others in the chemical sector and report lower satisfaction scores when they earn less than similar managers. We find hardly any evidence for the relevance of status quo preferences.
Keywords: M5; J28; J31; 330; compensation; job satisfaction; reference points; social comparisons; status quo preferences; Managervergütung; Prospect Theory; Arbeitszufriedenheit; Interpersoneller Nutzenvergleich; Chemieindustrie; Deutschland